Meta-Analysis Correlations between Hypertension, Smoking, and Severity Risk of COVID-19 - Lisa Safaah Novia Larsiani; Didik Gunawan Tamtomo; Bhisma Murti (Masters Program in Public Health, 2022)
Background: Based on the reported cases, 16.9% of COVID-19 patients were accompanied by comorbidities. Hypertension and smoking are suspected to be one of the pathological determinants that play a role in clinical predictors that are predicted to cause a worsening of the patient's condition during the treatment period. This study aimed to examine correlations between hypertension, smoking, and severity risk of COVID-19.Subjects and Method: Meta-analysis was carried out using PRISMA flow diagrams. Article searches through journal databases include: PubMed, Science Direct, Google Scholar. articles used in 2020-2022. The PICOs in this study were, Population: COVID-19 patients, Intervention: hypertension and smoking Comparation: not hypertension and not smoking, Outcome: severity of COVID-19. The keywords in this study were “hypertention” OR “high blood pressure” AND “severe COVID-19” OR “severty COVID-19” OR “patient COVID-19 outcome” “cigarette” OR “smoking” OR “current smoker” OR former smoker” AND “severe COVID-19” OR “severty COVID-19” OR “patient COVID-19 outcome” Inclusion criteria were articles used in full paper articles with a cohort design, relationship size used with aOR, intervention given the association of hypertension and smoking on the severity of COVID-19. Eligible articles were analyzed using the Revman 5.3 application.Results: A meta-analysis of 12 cohort articles originating from Asia, America, Africa, Europe, concluded that COVID-19 treatment patients with hypertension had higher severity 1.82 times compared to those without hypertension (aOR= 1.82; 95% CI= 1.18 to 2.79; p=0.006). Likewise, COVID-19 treatment patients with smoking habit had higher severity than those who do not smoke (aOR= 0.62; 95% CI= 0.14 to 2.65; p=0.520).Conclusion: COVID-19 patients with hypertension have an increased risk of severity. COVID-19 patients with smoking lower risk of severity. Keywords: Severe COVID-19, hypertention, cigarette. Correspondence:Lisa Safaah Novia Larsiani. Masters Program in Public Health. Universitas Sebelas Maret, Jl.Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: nl.lisasafaah@gmail.com Mobile: 089536503803.